1972
DOI: 10.1172/jci107043
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of individual free fatty acids by skeletal muscle and liver in man

Abstract: A B S T R A C T Arterial-venous concentration differences for individual free fatty acids (FFA) were measured across the deep tissues of the forearm, the splanchnic vascular bed, and the kidney in healthy, postabsorptive subjects. In addition, arterial-portal venous FFA differences were determined in five patients undergoing elective cholecystectomy.The differences in fractional uptake among the individual FFA across the forearm were small and not statistically significant. Splanchnic fractional uptake was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
71
1
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 25 publications
11
71
1
1
Order By: Relevance
“…Plasma stearate and myristate clearance rates were lower and higher, respectively, than the clearance rate of other fatty acids, and the use of stearate and myristate tracers underestimated and overestimated, respectively, measured total FFA R a values. Data from earlier studies have shown that the fractional uptake of different fatty acids by forearm tissues was not different, whereas splanchnic myristate uptake was greater and splanchnic stearate uptake was smaller than the uptake of other fatty acids (35,36). In addition, when injected simultaneously into rats, 14 C-stearate disappeared more slowly from plasma than 3 H-palmitate (37).…”
Section: Discussionmentioning
confidence: 89%
“…Plasma stearate and myristate clearance rates were lower and higher, respectively, than the clearance rate of other fatty acids, and the use of stearate and myristate tracers underestimated and overestimated, respectively, measured total FFA R a values. Data from earlier studies have shown that the fractional uptake of different fatty acids by forearm tissues was not different, whereas splanchnic myristate uptake was greater and splanchnic stearate uptake was smaller than the uptake of other fatty acids (35,36). In addition, when injected simultaneously into rats, 14 C-stearate disappeared more slowly from plasma than 3 H-palmitate (37).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, plasma FFA levels were decreased by fenofibrate. Because the uptake of fatty acids by the liver is proportional to their concentration in plasma (33), it is probable that the total amount of plasma fatty acids delivered to the liver for oxidation or reesterification was also decreased. Several mechanisms could have contributed to this fall in plasma FFAs.…”
Section: Discussionmentioning
confidence: 99%
“…Sampling from the portal vein is not easy in humans, but it has been performed in a small number of metabolic studies. In these studies, concentrations of NEFA or glycerol (another product of lipolysis) in the portal vein have been found to be close to those in arterial plasma (Hagenfeldt et al 1972;Björkman et al 1990;Blackard et al 1993). One example is the study of Blackard et al (1993): during laparotomy in obese women the portal vein was catheterized and samples taken.…”
Section: A Critical Look At the Portal Theorymentioning
confidence: 94%